2014
DOI: 10.1037/a0036418
|View full text |Cite
|
Sign up to set email alerts
|

Self-critical perfectionism and binge eating symptoms: A longitudinal test of the intervening role of psychological need frustration.

Abstract: Although abundant research has shown that self-critical perfectionism relates to binge eating symptoms, fewer studies have addressed the role of intervening processes that might explain why this is the case. Grounded in self-determination theory, we hypothesized that self-critical perfectionism would relate to an increased risk for binge eating symptoms because it engenders frustration of the psychological needs for autonomy, competence, and relatedness. This hypothesis was tested in a sample of 566 adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 73 publications
15
64
1
Order By: Relevance
“…As expected, gaming motivations and daily needs frustration are positively associated with PVG. These associations are consistent with work in other areas of study (Boone et al, 2014;Clarke, 2004;Costa et al, 2016;González-Cutre & Sicilia, 2012;Symons Downs, Savage, & DiNallo, 2013). However, in building upon previous research, the present findings are the first to show that the experience of daily autonomy frustration partially mediates the association between both introjected regulation of and amotivation toward gaming and PVG.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As expected, gaming motivations and daily needs frustration are positively associated with PVG. These associations are consistent with work in other areas of study (Boone et al, 2014;Clarke, 2004;Costa et al, 2016;González-Cutre & Sicilia, 2012;Symons Downs, Savage, & DiNallo, 2013). However, in building upon previous research, the present findings are the first to show that the experience of daily autonomy frustration partially mediates the association between both introjected regulation of and amotivation toward gaming and PVG.…”
Section: Discussionsupporting
confidence: 79%
“…Only two studies have shown a mediational role of needs frustration in explaining the presence of a problematic behavior, and both used reports of perfectionism as a predictor of needs frustration within a sport-specific context (Costa et al, 2016) or in daily life (Boone et al, 2014). Results demonstrated that perfectionism contributed to a problematic behavior (e.g., binge eating, exercise dependence) through an increase in needs frustration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact clinical studies applying SDT attest to the positive consequences of autonomy-supportive treatment climates, including higher treatment attendance, less dropout, less relapse, and enhanced well-being over the course of treatment. Such results have been obtained in various domains such as drug and alcohol dependence (Foote et al, 1999;Ryan, Plant, & O'Malley, 1995;Zeldman, Ryan, & Fiscella, 2004), weight loss (Williams, Grow, Freedman, Ryan, & Deci, 1996), smoking cessation (Williams, McGregor, et al, 2006), general medication adherence (Williams, Rodin, Ryan, Grolnick, & Deci, 1998), HIV-related medication adherence (Kennedy, Gogin, & Nollen, 2004), eating disorders (Van der Kaap-Deeder et al, 2014), and other issues.…”
Section: Translational Implications: Autonomy and Autonomy Support Inmentioning
confidence: 99%
“…Performing below those standards is not well tolerated and results in self-criticism and negative affect. Such traits have been associated with those at risk for eating disorders and have been demonstrated in adolescents with BED specifically [15].…”
Section: Self-critical Perfectionismmentioning
confidence: 98%